Relationship-Specific Investment - Crawford, Vincent P. (Quarterly Journal of Economics, 1990)
Journal Article Relationship-Specific Investment Get access Vincent P. Crawford Vincent P. Crawford University of California, San Diego Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 105, Issue 2, May 1990, Pages 561–574, https://doi.org/10.2307/2937801 Published: 01 May 1990